Genes of dopamine receptors and transporter in patients with schizophrenia: associations with the clinical characteristics of the disorder - A. S. Boiko; I. V. Pozhidaev; O. Z. Paderina; A. V. Semke (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Genotyping of 28 polymorphisms of 5 dopamine receptor genes and 12 polymorphisms of dopamine transporter gene was performed in 475 schizophrenia patients and 135 healthy individuals. Associations of several polymorphisms of the DRD2, DRD3 and SLC6A3 genes were identified with leading symptoms and late debut of schizophrenia.